IMPROVING YOUNG LEARNERS’ INTEREST IN READING - Anak Agung Istri Bulan Fitria Dewi; Ni Ketut Riska Dewi Prawita (Yavana Bhasha : Journal of English Language Education, 2019)
The aim of this study is to enhance the young learners to make them interestin reading the books by several methods. These methods may help to increase theself-interest in reading. In globalization era, the development of the teaching andlearning of English has been transformed. Nowadays, learners should not onlyfocus on the learning of speaking and writing but also reading due to requirementsof education that they should be able to understand and respond to the texts. Thereare many reasons the young learners have less interesting in reading, for examplethe development of the information forces the focus of teaching and learning on thecritical reading. The most common thing is the students may not know their interestin reading before they start to read the books. Reading interests play a veryimportant role in reading instruction and improvement. Furthermore, theunderstanding of young learners’ interest and abilities is required to help them inreading. This article entitled Improve Young Learners’ Interest in Reading consists ofthe great way of method to encourage the young learners to read through the useof wall magazine, the use of flash card, and the use of humor that can applied instrategies of reading aloud, reading the book several times, reading favorite books,and show many picture books.